1994
DOI: 10.1021/jo00096a043
|View full text |Cite
|
Sign up to set email alerts
|

p-Quinonemethide Analog of the CC-1065 and Duocarmycin Alkylation Subunits

Abstract: The synthesis and preliminary evaluation of 10 and 11, stable precursors to the inherently reactive but isolable p-quinonemethide analog 9 of the CC-1065 and duocarmycin alkylation subunits, are detailed. The p-quinonemethide 9, while reactive {ty% < 1 min, CH3OH), represents one of the few unsubstituted quinonemethides sufficiently stable for isolation and characterization. The structural origin of this stability and the ramifications of the observations on the origin of the stability of the CC-1065 and duoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Most of these compounds have only been observed in dilute solutions. So far, no simple QMs, i.e., not bearing substituents at the methylene group, have been isolated, except in two cases when fused aromatics are involved, making the quinonoid structure negligible . Even those having stabilizing substituents at the methylene group are known to undergo fast reactions with both nucleophiles and electrophiles giving products of 1,6-addition.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these compounds have only been observed in dilute solutions. So far, no simple QMs, i.e., not bearing substituents at the methylene group, have been isolated, except in two cases when fused aromatics are involved, making the quinonoid structure negligible . Even those having stabilizing substituents at the methylene group are known to undergo fast reactions with both nucleophiles and electrophiles giving products of 1,6-addition.…”
Section: Introductionmentioning
confidence: 99%
“…The duocarmycins and CC-1065 ( 1 − 3 ) are the parent members of an exceptionally potent class of antitumor antibiotics which derive their biological activity through the sequence selective alkylation of duplex DNA. A key feature shared by 1 − 3 is the amide linking the DNA binding and alkylation subunits. The important contribution of the N 2 atom to the unusual stability of the alkylation subunit via vinylogous amide conjugation has been described, and studies have revealed an apparent appropriate balance of reactivity versus stability with the presence of the linking N 2 amide. Replacement of the linking amide with a methylene in CBI-TMI ( 4 ) provided an analogue 5 possessing a fully engaged vinylogous amide which exhibited extraordinary stability ( t 1/2 = 3.5 years, pH 3), a loss of virtually all biological activity, and the inability to alkylate DNA even under extreme reaction conditions (37 °C, 0.1 M, 2 weeks) . Alternatively, removal of the nitrogen atom provided an exceptionally reactive carbocycle alkylation subunit ( t 1/2 = 4.0 h, pH 7) .…”
mentioning
confidence: 99%
“…Moreover, the observations are inconsistent with alternative models based on the premise that the natural enantiomer alkylation subunit controls the alkylation selectivity. Similarly, the unnatural enantiomer of the reversed agent ent-(-)-CDPI2-DSA (26) was found to alkylate the same sites as (+)-DSA-CDPI2 (25) [77][78][79], and the extensive number of investigations directed at the subunits of the natural products (33), studies that have provided analogs (80,81) and agents containing deepseated structural modifications have proven unusually valuable in defining the relationships between structure, functional reactivity, and biological properties (82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97). The acid-catalyzed activation of the DNA alkylation reaction led to the intuitive proposal that there may exist a direct relationship between the reactivity and cytotoxic activity of the agents and established the expectation that the biological potency may be enhanced as the electrophilic reactivity is increased (81).…”
mentioning
confidence: 99%
“…However, studies conducted with the agents 27-32, which were prepared by synthesis employing technology developed in the natural product total syntheses, revealed the reverse relationship and that the agents possessing the greatest stability may be expected to exhibit the most potent cytotoxic activity. Moreover, a well-defined direct relationship between solvolysis stability (pH 3) and biological (42,43,60), the structural origins of the unusual stability of the natural alkylation subunits (94), the stereoelectronic control that dictates nucleophilic addition to the least substituted cyclopropane carbon (94), subtle structural features that can modulate reactivity of the alkylation subunits (94,95), the SN2 versus SN1 mechanism of cyclopropane ring opening (94), and extensions of the studies to rationally designed DNA crosslinking agents (96,97) and prodrugs. Future studies with additional structural analogs of CC-1065 and the duocarmycins will continue to provide further insights into the origin of their properties.…”
mentioning
confidence: 99%